2009
DOI: 10.1007/s00467-008-1044-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased chymase-positive mast cells in children with crescentic glomerulonephritis

Abstract: Mast cell-derived chymase is an angiotensin II-forming enzyme that appears to be involved in tubulointerstitial fibrosis in the kidneys. Previous studies have shown that the level of chymase increases in grafted kidneys after rejection and in adult patients with diabetic nephropathy. However, the significance of chymase in children with renal diseases has not been investigated. Using immunohistochemistry, we have investigated chymase expression in biopsy samples of renal tissue from 104 children with kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…The study showed that the number of chymase-positive mast cells correlates with the mean intensity of the interstitial fibrosis, which is similar to the results obtained in our study [12].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The study showed that the number of chymase-positive mast cells correlates with the mean intensity of the interstitial fibrosis, which is similar to the results obtained in our study [12].…”
Section: Discussionsupporting
confidence: 81%
“…Mast cells can be divided into two classes, chymase-positive and chymase-negative, due to the fact that only a portion of mast cells are positive for chymase [9][10][11]. Chymase has the ability to convert angiotensin I to angiotensin II, which regulates intrarenal blood flow, and also participates in renal interstitial fibrosis [11,12]. It is involved in renal remodeling by increasing the expression of transforming growth factor β (TGF-β) [13].…”
Section: Introductionmentioning
confidence: 99%
“…MCs as a kind of inflammatory cells have been ignored or forgotten by nephrologists for a long time because they are not easily detected by routine histochemical staining. The associations between MC infiltration and the degree of tubulointerstitial damage in some renal diseases such as diabetic nephropathy, hypertensive nephropathy, IgA nephropathy and crescentic glomerulonephritis, support the idea that MCs are likely to be key players in the pathogenesis of interstitial fibrosis [17][18][19][20] . To our knowledge, there are no reports in the current literature that have de- scribed whether MCs participate in renal interstitial fibrosis induced by proteinuria.…”
Section: Discussionmentioning
confidence: 88%
“…The number of mast cells closely correlates with the severity of tubulointerstitial disease in renal diseases, including IgA nephropathy [31, 32], primary and secondary glomerulonephritis [18, 19, 33, 34], diabetic nephropathy [35,36], hypertensive nephropathy [26] and allograft rejection [16, 20, 37, 38]. Mast cell accumulation is also inversely correlated with a decline in glomerular filtration rate and disease progression [31, 34, 39-41].…”
Section: Mast Cell Density Correlates With Renal Tubulointerstitial Dmentioning
confidence: 99%